POTENSI EKSTRAK RUMPUT LAUT (Eucheuma cottoni) SEBAGAI ANTIOKSIDAN - Aminah Aminah; Hamsinah Hamsinah; Nurmila A. Abiwa; Sulasmi Anggo (Fakultas Farmasi UMI, 2020)
Seaweed (Eucheuma cottoni) is a marine biota that is often used as an additive to pharmaceutical products that function as thickener. But seaweed, which is rich in carrageenan, also contains vitamin C which has the potential as an antioxidant. The method used was to test the antioxidant activity of seaweed extract (Eucheuma cottoni) with the DPPH (1,1-Diphenyl-2-Picrylhdrazil) damping method. The test sample was in the form of seaweed ethyl acetate extract, where the standard standard of comparison of quarsetin and seaweed extract samples was made in 5 variations of concentration. The standard curve produced by quarsetin with concentrations of 2, 4, 6, 8, 10 ppm at the maximum wavelength DPPH 514,942 nm. The results obtained by the Kuarsetin standard with regression values y = 6.4765x + 7.567, the correlation value r = 0.99959 and IC50 = 6.48 (very strong antioxidant activity) while the ethyl acetate extract of seaweed with concentrations of 600, 800, 1000, 1200, 1400 ppm % inhibition was obtained with regression values y = 0.0104x + 16.708, the correlation value r = 0.9972 and IC50 = 3201.15 (very weak antioxidants). So it can be concluded that the seaweed ethyl acetate extract has the potential for antioxidant activity.